Hoffbrand's Essential Haematology - Hoffbrand, A. V Moss, Paul A. H (WILEY Blackwell, 2016)
The definitive haematology textbook of choice for medical students Hoffbrand's Essential Haematology has built a reputation as the flagship haematology textbook for both students and junior doctors, providing an authoritative introduction to the subject.